Immunomodulation of dendritic cells by Lactobacillus reuteri surface components and metabolites. Issue 2 (19th January 2021) - Engevik, Melinda A.; Ruan, Wenly; Esparza, Magdalena; Fultz, Robert; Shi, Zhongcheng; Engevik, Kristen A.; Engevik, Amy C.; Ihekweazu, Faith D.; Visuthranukul, Chonnikant; Venable, Susan; Schady, Deborah A.; Versalovic, James
Abstract: Background: Lactic acid bacteria are commensal members of the gut microbiota and are postulated to promote host health. Secreted factors and cell surface components from Lactobacillus species have been shown to modulate the host immune system. However, the precise role of L . reuteri secreted factors and surface proteins in influencing dendritic cells (DCs) remains uncharacterized. Hypothesis: We hypothesize that L . reuteri secreted factors will promote DC maturation, skewing cells toward an anti‐inflammatory phenotype. In acute colitis, we speculate that L . reuteri promotes IL‐10 and dampens pro‐inflammatory cytokine production, thereby improving colitis. Methods & Results: Mouse bone marrow‐derived DCs were differentiated into immature dendritic cells (iDCs) via IL‐4 and GM‐CSF stimulation. iDCs exposed to L . reuteri secreted factors or UV‐irradiated bacteria exhibited greater expression of DC maturation markers CD83 and CD86 by flow cytometry. Additionally, L . reuteri stimulated DCs exhibited phenotypic maturation as denoted by cytokine production, including anti‐inflammatory IL‐10. Using mouse colonic organoids, we found that the microinjection of L . reuteri secreted metabolites and UV‐irradiated bacteria was able to promote IL‐10 production by DCs, indicating potential epithelial‐immune cross‐talk. In a TNBS‐model of acute colitis, L . reuteri administration significantly improved histological scoring, colonic cytokine mRNA, serum cytokines, and bolstered IL‐10 production. Conclusions: Overall these data demonstrate that both L . reuteri secreted factors and its bacterial components are able to promote DC maturation. This work points to the specific role of L . reuteri in modulating intestinal DCs. New & Noteworthy: Lactobacillus reuteri colonizes the mammalian gastrointestinal tract and exerts beneficial effects on host health. However, the mechanisms behind these effects have not been fully explored. In this article, we identified that L . reuteri ATTC PTA 6475 metabolites and surface components promote dendritic cell maturation and IL‐10 production. In acute colitis, we also demonstrate that L . reuteri can promote IL‐10 and suppress inflammation. These findings may represent a crucial mechanism for maintaining intestinal immune homeostasis. Abstract : L . reuteri secreted factors and its bacterial components are able to promote DC maturation and IL‐10 production. Additionally, L . reuteri is able to elevate IL‐10 and suppress inflammation in a TNBS model of colitis.